Kinematic analysis and bilateral differences in pedaling technique of professional cyclists - Javier Yanci Irigoyen (Pensar en Movimiento)
The objectives of this study were to describe the maximal angulations of knee and ankle in the flexions and extensions in pedaling performed by professional cyclists and to compare the differences in these angulations between the right and left leg. Thirteen cyclists, who all belonged to a professional team which regularly competed in the “Vuelta Ciclista a España”, took part in this study. Measurements were taken of the length of the crank arms, height and saddle height of the cyclists’ bicycles. A 2D kinematic analysis was also performed of their pedaling to study the angulations of knee and ankle. No significant differences were found between the right and the left leg with regard to the angulations of flexion or extension of the knees or the flexion of the ankles. However, contrary to other studies, differences were found in the ankle angulation of extension (p < 0.05, difference between means = 14.53%, d = 0.37, moderate) between the two legs. In future research it would be interesting to complement the kinematic analysis with a kinetic study to observe if the differences in the angulations are accompanied by differences in the force applied by each leg.